Pengenalan PHBS (Pola Hidup Bersih dan Sehat) untuk Mencegah Penularan COVID-19 dengan Metode TGT (Teams Games Tournament) di UPT 315 Gresik - Lailatun Nimah; Ika Nur Pratiwi; Lingga Curnia Dewi (Pelita Medika, 2021)
Background : Cases of positive cases of Corona Virus Disease (COVID-19) in children are increasing day by day. The increase in the number of COVID-19 sufferers in children shows a lack of understanding of children about preventing the transmission of COVID-19. Assistance has been provided by the government for the purchase of facilities and infrastructure as an effort to prevent the transmission of COVID-19 in schools, but health education has not been comprehensive. Health education for children about preventing the transmission of COVID-19 needs to be done. Method : The approach taken is to conduct health education about the introduction of PHBS (Clean and Healthy Lifestyle) to prevent the transmission of COVID-19 with the TGT (Teams Groups Tournament) method. Result : From the data obtained from 42 children who participated in the activity, the majority there was an increase in the level of knowledge about PHBS to prevent the transmission of COVID-19. Actions after the activity on how to wash hands properly, cough and sneeze etiquette and how to wear the right mask are also good Conclusion : Health education in the school environment needs to be carried out in a fun method so that it is easily understood by students.